Does environmental regulation develop a greener energy efficiency for environmental sustainability in the post-COVID-19 era: Role of technological innovation - Zhang, Mingxia; Du, Mingyue (Frontiers in Environmental Science, 2022)
Improving green energy efficiency (GEE) and promoting green economic transformation are important goals for China to achieve sustainable economic development in the post-COVID-19 era. Based on panel data of 27 manufacturing industries in China, this paper uses GMM model and threshold model to study the impact of environmental regulation and technological innovation on green energy efficiency. Our findings show that technological innovation promotes green energy efficiency in both pollution-intensive and clean industries, and its promotion effect is more pronounced in pollution-intensive industries. Environmental regulation not only directly improves the green energy efficiency of polluting industries and clean industries, but also plays a positive intermediary role between technology and green energy efficiency. The impact of technological innovation on GEE has a threshold effect of environmental regulation. When environmental regulation crosses the threshold, technological innovation does not significantly promote GTFP. The promotion effect of technological innovation on GEE will increase with the strengthening of environmental supervision. Therefore, the government should formulate reasonable environmental regulations according to the industry heterogeneity to vigorously promote the green energy efficiency of the manufacturing industry.